2020
DOI: 10.3390/min10100856
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Microbial “Contact Leaching” to Pyrite Oxidation under Different Controlled Redox Potentials

Abstract: The function of microbial contact leaching to pyrite oxidation was investigated by analyzing the differences of residue morphologies, leaching rates, surface products, and microbial consortia under different conditions in this study. This was achieved by novel equipment that can control the redox potential of the solution and isolate pyrite from microbial contact oxidation. The morphology of residues showed that the corrosions were a little bit severer in the presence of attached microbes under 750 mV and 850 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Direct FeS 2 utilization or indirect, through FeS 2 dissolution mechanisms, have been proposed. However, it is difficult to determine which is the most probable route and to distinguish between the two 10 , 37 . The high denitrification rates obtained in this study could be partially attributed to the active denitrifying mixed community present in the biomass that was used to inoculate the P-FBR, which was obtained from the study of Carboni et al 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct FeS 2 utilization or indirect, through FeS 2 dissolution mechanisms, have been proposed. However, it is difficult to determine which is the most probable route and to distinguish between the two 10 , 37 . The high denitrification rates obtained in this study could be partially attributed to the active denitrifying mixed community present in the biomass that was used to inoculate the P-FBR, which was obtained from the study of Carboni et al 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these results are rather limited to allow for commentary on the exact mechanism of FeS 2 obtained in the studied reactor during the total course of the experimental period. Surface and composition analysis of the FeS 2 before and after operation could reveal changes in the morphology of the FeS 2 and give an indication of the parts of FeS 2 utilized by the microbial community for denitrification 37 . Studies that combine microbial community analysis with surface analysis in controlled media are essential in deciphering the FeS 2 -driven denitrification mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence supports the notion that the efficient bacterial sulfur oxidation activities in the leaching process require the development of a complex and orchestrated biofilm matrix. This involves either native or externally introduced acidophiles colonizing the ore surface ( Bobadilla-Fazzini, 2014 ; Dong et al, 2020 ; Bobadilla-Fazzini and Poblete-Castro, 2021 ), or relates to the aggregation degree of planktonic cells prior to biofilm formation ( Bellenberg et al, 2015 ; Melaugh et al, 2016 ; Yavari et al, 2019 ). Consequently, it is less likely that the improved desulfurization process can be solely attributed to the activity of sulfur-oxidation bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors that affect pyrite dissolution, the solution Eh is the most critical and is directly correlated with rate. Below the redox potential of 650 mV (vs. SHE), pyrite is barely oxidized, even though microbes adhere on the pyrite surface [31,32]. It was reported that the pyrite oxidation was 5 times faster with the elevation of redox potential by 100 mV [33].…”
Section: Microbial Community and Activitymentioning
confidence: 99%